Improving Learning Achievement of Class IX.F Students of SMP Negeri 2 Kendari in Science Subjects through a Cooperative Learning Model Team Games Tournament (TGT) Type - sudirman sudirman (Persatuan Guru Republik Indonesia Provinsi sulawesi Tenggara, 2022)
This study aims to determine the use of the Teams Games Tournament (TGT) cooperative learning model in science subjects to improve student achievement in class IX.F SMP Negeri 2 Kendari. This research was conducted in class IX.F SMP Negeri 2 Kendari. The subjects studied were students of class IX.F, totaling 34 students with the details of 19 women and 15 men. The results showed that in three learning cycles: 1) the learning outcomes achieved by students in the first cycle who scored 70 were 17 students (50.00%), 2) the learning outcomes achieved by students in the second cycle who scored 70 as many as 22 students (64.7%), and 3) the learning outcomes achieved by students in the third cycle who scored 70 were 29 students (85.3%). This research shows that there has been an increase in learning outcomes in the first cycle compared to the initial test, where students who have completed learning are 17 students compared to the initial test of 14 students. In the third cycle, there has been an increase in learning outcomes when compared to the second cycle, where the number of students who completed classically was 29 students (85.3%) with an average value of 75.0 when compared to the second cycle of students who completed 22 students (64, 7%) with an average score of 69.6. The results of the study concluded that using the Team Games Tournament (TGT) cooperative learning model in science subjects could improve student achievement in class IX.F SMP Negeri 2 Kendari.